Topological aspects of dynamical systems on manifolds - Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Necessary and sufficient conditions are presented for the existence of dynamical systems on manifolds, for which the set of nonwandering points consists of a disconnected union of 2-dimensional tori with a hyperbolic structure.